Bimbingan Karir sebagai Upaya Meningkatkan Kesiapan Kerja Generasi Z di Era Digital - Nur; Allen Kristiawan; Anny Nurbasari; Rusli Ginting Munthe; Christin Septina Basani (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Education serves as a fundamental foundation for both career success and character development. Generation Z faces considerable challenges in making career decisions due to an overwhelming number of available options, limited awareness of their own talents, parental expectations, and the negative influence of social media. To address these challenges, Maranatha Christian University in collaboration with GKI Kebon Jati Bandung organized a career management seminar for Generations Z and Alpha. The program employed several methods, including lectures, aptitude assessments (Johari Window and RIASEC), and triadic discussions involving experts, parents, and students. The triadic approach proved to be highly effective in fostering objective dialogue. The findings suggest a significant improvement in participants’ career decision-making (28.8%), ability to manage pressure (21.6%), and confidence in their personal interests and talents (17.6%). These results highlight the importance of integrative and collaborative approaches in preparing younger generations for their future careers.